Adolescents, family, status and health: new insights into health behaviour in school-aged children in Portugal - Matos, M. G.; Borges, A.; Capucha, Luís (Vulnerable Children and Youth Studies, 2011)
The purpose of this study is to examine the influence of the family's economic and cultural/educational status on adolescent health. The sample was composed of adolescents who participated in the study in continental Portugal, integrating the European study of Health Behaviour in School-aged Children (HBSC). The study included a total of 4877 students attending the 6th, 8th and 10th grades from Portuguese public schools, with an average age of 14 years. The instrument used was the HBSC questionnaire. The results showed that the family's economic and cultural/educational status has a significant impact on adolescent health and perception of health-related quality of life. Children from more economically deprived families tend to have a lower perception of quality of life and less life satisfaction. However, the culture/education results are more complex and, interestingly, follow different directions. These results allow us to claim that increasing parental schooling and economical well-being would be one of the protective policy strategies to promote adolescent health and well-being, although there is a risk of decreasing the related quality of life perception when parents are at the same time "too" cultivated and "too" wealthy, suggesting a new familial vulnerability that should also be addressed.